Oxidasi Biologi, Radikal Bebas, dan Antioxidant - Eni Widayati (Majalah Ilmiah Sultan Agung, 2012)
Introductions : Aerobic metabolism process induces production of free radicals (ROS) 2.5% of oxygen consumption or about 3.4 kg/24 hours. Content : Stressor likes ultraviolet radiation, hypoxia, hyperoxia, pollutant, and other chemical substances could induce ROS production. Stressor also stimulates secretion of antioxidant enzymatic such as catalase, hydropheroxidase, and superoxide dismutase. The ROS produced will disturb homeostasis or stimulate cell growth, dependent on the level of ROS. When the ROS level is overwhelm the antioxidant capacity, cell leading to undergo oxidative stress. If the ROS level and antioxidant capacities are equilibrium, it leading to cell growth. Other resources of ROS result from biologic oxidation reaction particularly from mitochondria. To scavenge ROS, cell has provided several antioxidants water and lipid soluble both enzymatic and non-enzymatic.Conclusion : The ROS is produced in aerobically life resulted from oxidative phosphorilations chain reaction. Cell provides the antioxidant both enzymatic and non-enzymatic in order to scavenge it. Keywords : Biologic oxidation, ROS, Antioxidants